Executive control in schizophrenia: a preliminary study on the moderating role of COMT Val158Met for comorbid alcohol and substance use disorders. (4th July 2017) - Carrà, Giuseppe; Nicolini, Gabriella; Crocamo, Cristina; Lax, Annamaria; Amidani, Francesca; Bartoli, Francesco; Castellano, Filippo; Chiorazzi, Alessia; Gamba, Giulia; Papagno, Costanza; Clerici, Massimo
Abstract: Background: A functional polymorphism in the catechol-O-methyltransferase ( COMT ) gene (Val158Met) appears to influence cognition in people with alcohol/substance use disorders (AUD/SUD) and in those with psychosis. Methods: To explore the potential moderating effect of these factors, a cross-sectional study was conducted, randomly recruiting subjects with DSM-IV diagnosis of schizophrenia. AUD/SUD was rigorously assessed, as well as COMT Val158Met polymorphism. Executive control functioning was measured using the Intra-Extra Dimensional Set Shift (IED). The effect of a possible interaction between comorbid AUD/SUD and COMT Val158Met polymorphism on IED scores was explored. Results: Subjects with schizophrenia, comorbid AUD/SUD, and MetMet carriers for SNP rs4680 of the COMT gene showed worse performance on IED completed stages scores, as compared with individuals with ValVal genotype. However, among subjects without AUD/SUD, those with the MetMet variant performed better than people carrying ValVal genotype. Conclusions: This study is the first to date examining the impact of COMT on cognition in a highly representative sample of people with schizophrenia and comorbid AUD/SUD. Differential moderating effects of COMT Val/Met genotype variations may similarly influence executive functions in people with schizophrenia and comorbid AUD/SUD.